The Temperature Effect on Sensitivity of Direct Detection Optical Receiver Incorporating FET- Amplifier (University of Thi-Qar Journal for Engineering Sciences, 2012)
It is known that temperature rise boosts the generations of electron-holes pairs in semiconductors and increases their conductivity that obtained to increase noise.High Electron Mobility Transistors (HEMTs) gives many advantages like low noise and high associated gain at microwave frequencies.Different shapes and places in containers are done to analyze the temperature effect on chips with other thermal and aerodynamic parameters.In this paper,the performance of integrated optical receiver consisting of PIN(Positive Intrinsic Negative)-photo diode and HEMT-based transimpedance type amplifier is analyzed upon the effect of temperature variation. Variation of temperature occurs when change device space in one block covers.The simulation results show that the sensitivity (Psen) of an optical receiver is minimal in space when temperature effect is low if it is based on well-designed HEMT.